The female figure in the fantastic short stories of Maupassant - Santos, Kedrini Domingos dos; Oliveira, Andressa Cristina de (Lettres Françaises, 2017)
The French writer Guy de Maupassant (1850-1893), author of “Ball-of-Tallow” and Bel-Ami, is one of the great masters of the French fantastic short story. In Maupassant’s narratives, the fantastic appears sometimes as a way of revealing the reality; the fantastic is not opposed to the real, but it aims to show a tension between the possible and the impossible, between the ordinary and the extraordinary. Maupassant deploys some elements to create the fantastic, such as apparitions, ghosts, objects or parts of the human body, etc. In his fantastic stories, there are several precious themes to the writer, and the woman is one of them. This paper therefore will seek to analyze the presence of women in the fantastic short stories of Maupassant, examining the narrative strategies of the writer to create the fantastic.